Health-related quality of life outcomes and economic burden of inflammatory bowel disease in Japan - Yamabe K; Liebert R; Flores N; Pashos CL (Dove Medical Press, 2019)
Kaoru Yamabe,1 Ryan Liebert,2 Natalia Flores,2 Chris L Pashos3 1Healthcare Policy and Access, Takeda Pharmaceutical Company Limited, Nihonbashi, Chuouku, Tokyo 103-8668, Japan; 2Health Outcomes Research, Kantar Health, New York, NY 10010, USA; 3Global Outcomes and Epidemiology Research, Data Sciences Institute, Takeda Pharmaceuticals International Inc., Cambridge, MA, 02139, USA Purpose: Previous Japanese studies have not compared health-related quality of life (HRQoL), work productivity and activity impairment, health care resource utilization (HRU), and costs in inflammatory bowel disease (IBD) patients with non-IBD controls, leading to insufficient evidence regarding IBD’s true burden. The aim of this study was to examine the impact of IBD on patient-reported outcomes and costs among Japanese adults (≥18 years). Patients and methods: This retrospective cross-sectional study used data from the 2012–2014 Japan National Health and Wellness Survey (N=83,505). HRQoL (SF-36v2), work productivity and activity impairment (work productivity and activity impairment-General Health Questionnaire), HRU, and annual costs were compared between respondents with IBD (n=441) and non-IBD controls (n=82,944), and within IBD subtypes (Crohn’s disease [CD] and ulcerative colitis [UC]) using chi-square and ANOVA tests. Results: Mental Component Summary (MCS), Physical Component Summary (PCS), and health state utility (Short-Form-6 Dimensions [SF-6D]) scores were significantly lower in IBD respondents than in controls (differences of 2.2 points, 2.6 points, and 0.041 points, respectively; all P<0.001). However, only differences in SF-6D scores reached the minimally important difference threshold. Furthermore, IBD-diagnosed respondents reported greater absenteeism, presenteeism, overall work productivity loss and activity impairment, and HRU than controls (all P<0.001). Consequently, direct and indirect costs were 3-fold and 1.5-fold higher in IBD-diagnosed respondents than in controls (both, P<0.001). Additionally, CD-diagnosed respondents had lower MCS, PCS, and SF-6D scores (all P<0.01) and higher direct costs (P<0.001) than UC-diagnosed respondents. Conclusion: IBD and its subtype CD were associated with lower HRQoL, greater impairment to work and non-work activities, HRU, and costs among Japanese adults. This reinforces the general consensus that IBD patients, specifically those diagnosed with CD, require support from their family and society to combat the disease. Keywords: activity impairment, costs, health care resource utilization, health-related quality of life, inflammatory bowel disease, work productivity impairment